Locus of Control and Internet Addiction among University Students: Investigating the Relationship between Locus of Control and Internet Addiction Among University Students (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present research is to examine the relationship between internal and external locus of control and internet addiction among university students. The objective is the study is to find out the level of internet addiction among students with internal and external locus of control. Based on the previous studies, a hypothesis was framed that there is no significant difference in internet addiction among students with internal and external locus of control, the sample consists of 60 students, who were studying in Bangalore University Campus. Students were administered a Julian B. Rotter’s Locus of control scale (1966) and Dr. Kimberly S. Young’s Internet addiction test (1998).The obtained data were analysed using ‘t’ test ,The obtained result shows that there is no significant difference in internet addiction among students with internal and external locus of control.